Arthrobotrys xiangyunensis, a novel nematode-trapping taxon from a hot-spring in Yunnan Province, China - Liu, Shuoran; Su, Hongyan; Su, Xijun; Zhang, Fa; Liao, Guanghui; Yang, Xiaoyan (Phytotaxa, 2014)
An Arthrobotrys species with adhesive nets (trapping device) was isolated from hot-spring waterlogged soil during research on evolutionary patterns of nematode-trapping fungi in Yunnan Province, China. Morphological and phylogenetic analyses indicate this is a novel predatory species of Arthrobotrys, which we herein introduce as A. xiangyunensis. The new species is characterized by occasionally branched conidiophores, colorless, fusiform to oval or clavate conidia which mostly have 1–5 septa and measure 27–72(55.8) × 14.5–28.5(21.9) μm. The new species is introduced with illustrations in this paper. Its morphology is rather similar to Monacrosporium guizhouense, M. longiphorum, M. sphaeroides, M. eudermatum and Arthrobotrys mangrovispora, but the phylogenetic analysis shows that A. xiangyunensis and its morphological relatives are distinct.